Cognitive behavioral therapy for psychosis to divert delusions in schizoaffective depressive type - Takdir, Annisya Muthmainnah; Yuniardi, Muhammad Salis (Universitas Muhammadiyah Malang, 2024)
The schizoaffective disorder is a mental disorder characterized by a combination of symptoms of Schizophrenia and affective disorders. One symptom is delusions, which can lead to maladaptive behaviour. This research aims to overcome delusional symptoms which have an impact on sleepless behaviour. The assessment methods were clinical interviews, observation, WAIS test, Graphic test (Draw a Person (DAP) and BAUM), WWQ test, TAT test, Beck Depression Inventory (BDI), and World Health Organization Disability Assessment Scale 2.0 (WHODAS). Cognitive Behavioral Therapy for Psychosis (CBTP) intervention using cognitive reframing techniques and behavioural coping skills has been proven to be able to overcome the problems experienced by the subject. CBT helps subjects ignore, distract, and adapt to delusions but does not suppress or confront the delusions themselves. The subject diverts the delusion by thinking about a better goal in life, thereby helping to reduce the behaviour of sleeplessness experienced by the subject. Gangguan skizoafektif merupakan gangguan jiwa yang ditandai dengan kombinasi gejala Skizofrenia dan gangguan afektif. Salah satu gejalanya adalah delusi, yang dapat menyebabkan perilaku maladaptif. Penelitian ini bertujuan untuk mengatasi gejala delusi yang berdampak pada perilaku sulit tidur. Metode penilaian yang digunakan adalah wawancara klinis, observasi, tes WAIS, tes Grafis (Draw a Person (DAP) dan BAUM), tes WWQ, tes TAT, Beck Depression Inventory (BDI), dan World Health Organization Disability Assessment Scale 2.0 (WHODAS). Intervensi Cognitive Behavioral Therapy for Psychosis (CBTP) dengan menggunakan teknik kognitif reframing dan keterampilan behavioral coping terbukti mampu mengatasi permasalahan yang dialami subjek. CBT membantu subjek mengabaikan, mengalihkan perhatian, dan beradaptasi terhadap delusi namun tidak menekan atau menghadapi delusi itu sendiri. Subjek mengalihkan khayalan tersebut dengan memikirkan tujuan hidup yang lebih baik sehingga membantu mengurangi perilaku sulit tidur yang dialami subjek.